The Life Cycle and Larval Development of Neoechinorhynchus iraqensis (Acanthocephala: Neoechinorhynchidae) in the Intermediate Host - Al-Sady, R. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
For the first time, the life cycle of Neoechinorhynchus iraqensis, a parasite of Liza abu and other freshwater fishes in Iraq and its larval development in the intermediate host, the copepod Cyclops hyalinus was given. Hatching took place in the intestine of the copepod host within 10 minutes of exposure to the infective eggs. Motile acanthor penetrated the wall of the intestine within 2-4 hr. after exposure and was found free in the hemocoel where it metamorphoses through the acanthella stage. Acanthella stage revealed changes in the entoblast where the anterior section gave rise to brain, proboscis and proboscis receptacle. The posterior section differentiation gave rise to the genital system. By  12 days, development in the copepod apparently was completed and by 13-14 days, the juvenile was infective for the definitive host.